Multiparametric Color Tendency Analysis (MCTA): A Method to Analyze Several Flow Cytometry Labelings Simultaneously - Henriques-Pons, Andrea; Beatrici, Carine P.; Sánchez-Arcila, Juan Camilo; da Silva, Fabricio Alves Barbosa (Frontiers in Bioengineering and Biotechnology, 2020)
Despite the remarkable evolution of flow cytometers, fluorescent probes, and flow cytometry analysis software, most users still follow the same ways for data analysis. Conventional flow cytometry analysis relays on the creation of dot plot sequences, based on two fluorescence parameters at a time, to evidence phenotypically distinct populations. Thus, reaching conclusions about the biological characteristics of the samples is a fragmented and challenging process. We present here the MCTA (Multiparametric Color Tendency Analysis), a method for data analysis that considers multiple labelings at the same time, extending and complementing conventional analysis. The MCTA executes the background fluorescence exclusion, spillover compensation, and a user-defined gating strategy for subpopulation analysis. The results are then presented in conventional FSC x SSC dot plots with statistical data. The method considers the fluorescence intensity of multiple labelings simultaneously for each event and generates a resultant vector mostly influenced by predominant labelings. This resultant vector is represented by a resultant color, making it easy to visualize phenotypic modulations amongst cellular subpopulations, especially in multiple samples. Besides, it is a deterministic method that analyzes all events in the file and assigns a resulting color to all that obey the gating strategy, with no polymer regions defined by the user. It also evidences rare events and subpopulations that could not be analyzed due to imprecise manual gating. We believe that the MCTA method adds a new perspective over multiparametric flow cytometry analysis while evidencing modulations of molecular labeling profiles based on multiple fluorescences. Availability and implementation: The instructions for the MCTA application is freely available at https://github.com/flowcytometry/MCTA.